G74(P) Improving paediatric prescribing confidence in non-paediatricians. (May 2019) - Trivedi, A; Banerjee, U
Abstract : Aim: Reported paediatric prescribing error rates are up to 13% and in our trust a baseline audit found our local error rate was 5.4%. A number of these errors are made by non paediatricians prescribing for paediatric patients. We wanted to increase their confidence in paediatric prescribing to try and reduce paediatric prescribing errors. Method: We organised interactive case based teaching sessions for both the emergency medicine doctors and surgical doctors who commonly prescribe for our paediatric patients. We asked doctors to self-rate their confidence from strongly agree to strongly disagree with regards to prescribing in paediatrics. We then asked them to self-rate their confidence after the teaching session. Results: Prior to the teaching sessions the majority of doctors said they either strongly disagreed or disagreed about their confidence in paediatric prescribing (25 out of 34 doctors). After the teaching sessions all doctors said they either agreed or strongly agreed that the session had increased their confidence in prescribing. Furthermore, we received many positive comments, in particular doctors appreciating the opportunity to practice prescribing for paediatric patients in an interactive environment. A repeat audit has shown a reduction in local error rate to an average of 3.4% from January to September 2018. We feel that the teaching sessions for non-paediatricians have helped to play a role with this. Conclusion: Increasing confidence in paediatric prescribing for non-paediatricians is extremely important. We used interactive case studies in our teaching sessions, although we know this does not replicate seeing an actual patient, giving doctors a safe environment in which to learn in and ask questions helped improved confidence in prescribing. We feel that these teaching sessions have also helped to reduce our local error rate.